Establishment of the institute of mediation in the Visegrad Group countries - Fihun, Nataliia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
In Slovakia, the Czech Republic, Hungary, and Poland, the development of alternative dispute resolution and the first attempts at mediation took place in the early 1990s, and the legal framework and organizations providing mediation services are still in place. As the process of institutionalization of the mediation procedure is still ongoing in Ukraine, it is important to analyze the experience of other countries in implementing mediation in their legal systems. The aim of the article is to analyze the process of formation of the mediation institution in Slovakia, the Czech Republic, Poland, and Hungary. The article describes the role of international partners in the development of the mediation institution in the Visegrad Group, in particular the international organization Partners for Democratic Change, which facilitated the establishment of mediation centers in the countries, conducted training campaigns and assisted in pilot mediation projects. In addition, the contribution of mediation centers and professional associations of mediators in the development of mediation and its promotion in society was noted. The article examines the main legal acts adopted by states to regulate the mediation procedure in various fields. For example, Slovakia, the Czech Republic, and Hungary have regulated the mediation process, the status of mediator, the rights and obligations of the parties in certain laws, while in Poland amendments have been made to procedural codes and by-laws regulating certain procedural issues. As a result of the study, several conditional stages of introduction of mediation into the legal systems of countries were identified: spreading the idea of alternative methods of resolving disputes in society, the introduction of pilot mediation projects, creation of professional associations and mediation centers, adoption of regulations. Prerequisites for implementation were: an information campaign to promote mediation services among the population, proper theoretical and practical training of mediators by professional institutions, the creation of a legal basis for the development of the institution of mediation.